(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
This study aims to analyze and empirically test how service quality and digital marketing influence purchasing decisions at Gulali Donut’s Perean Branch, Tabanan Regency. Gulali Donut’s Perean Branch experienced a decrease in revenue and customer visits due to unsatisfactory service quality and ineffective digital marketing strategies, so improvements are needed to increase purchasing decisions. This study uses a quantitative approach with multiple linear regression methods. The location of this research was conducted at the Gulali Donuts Shop, Perean Branch, which is precisely located at Jalan Denpasar - Singaraja, Baturiti, Perean Tengah. The sampling technique was carried out by purposive sampling based on the criteria of age 18-55 years, having shopped at least twice, and being willing to fill out a questionnaire. The results showed that service quality and digital marketing had a positive and significant influence on purchasing decisions at Gulali Donut’s Perean Branch, Tabanan.